The relationship between social phobia and cognitive impairment in idiopathic generalized epilepsy patients: a cross-sectional study - Kocatürk, İdris and İnaltekin, Ali (The European Research Journal, 2024)
Objectives: Epilepsy, a neurological disorder affecting approximately 65 million people worldwide, frequently presents with various comorbidities, including cognitive impairment. The factors contributing to cognitive impairment are complex and multifaceted. This study aimed to investigate the influence of social phobia on cognitive function in patients with idiopathic generalized tonic-clonic epilepsy. Methods: This prospective study recruited 87 adult idiopathic generalized tonic-clonic epilepsy patients diagnosed according to the International League Against Epilepsy 2017 classification. Differential diagnosis involved electroencephalography, magnetic resonance imaging, and neurological examinations. All participants were assessed for cognitive impairment, social phobia, depression, and anxiety using the Montreal Cognitive Assessment, Liebowitz Social Anxiety Scale, Beck Depression Inventory, and Beck Anxiety Inventory, respectively. Results: A significant majority (73.6%) of participants reported social phobia. Compared to those without social phobia, the Montreal Cognitive Assessment total score was significantly lower in the social phobia group (P=0.002). Additionally, epilepsy duration was significantly longer in the social phobia group (P=0.03). Montreal Cognitive Assessment scores showed a negative correlation with Liebowitz Social Anxiety Scale-avoidance, Liebowitz Social Anxiety Scale-total, and age (P=0.003, P=0.005, and P<0.001, respectively). Conclusions: This study suggests that individuals with idiopathic generalized tonic-clonic epilepsy experiencing social phobia may exhibit lower cognitive function compared to those without. This indicates that comorbid social phobia might negatively impact cognitive abilities in idiopathic generalized tonic-clonic epilepsy patients.